1985
DOI: 10.1111/j.1365-2621.1985.tb13045.x
|View full text |Cite
|
Sign up to set email alerts
|

HPLC Determination of Sugars in Raw and Baked Sweet Potatoes

Abstract: Isocratic HPLC techniques were developed for the quantitative analysis of sugars in raw and baked sweet potato roots. The major sugars in raw roots: sucrose, glucose, and fructose, were quantitated with a cation exchange resin column (Aminex HPX-87C) heated to 75°C using HPLC-grade Hz0 as the mobile phase and refractive index detection. The major sugars in baked roots (convection oven or microwaved) were maltose, sucrose, glucose, and fructose. They were quantitated with an aminopropyl bonded phase column (Bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
67
0
3

Year Published

1988
1988
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(78 citation statements)
references
References 5 publications
8
67
0
3
Order By: Relevance
“…The filtrate was collected, filtered through a 0.45 μm membrane filter, and injected into a high performance liquid chromatograph (HPLC). Sugar content was determined using a modified method provided by Picha (1985). Sugars were analyzed using HPLC (Pump model No.…”
Section: Sugar Composition Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The filtrate was collected, filtered through a 0.45 μm membrane filter, and injected into a high performance liquid chromatograph (HPLC). Sugar content was determined using a modified method provided by Picha (1985). Sugars were analyzed using HPLC (Pump model No.…”
Section: Sugar Composition Analysismentioning
confidence: 99%
“…Consumers enjoy the pleasant odor and flavor of baked sweet potatoes. Although chemical composition analysis of sweet potatoes has been previously documented (Ahmed et al 2010;Ahromrit and Nema 2010;Aina et al 2009;Picha 1985;Picha 1986;Vimala et al 2011), little information on the effect of baking has been reported (Lai et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…When a raw sweet potato root is analysed, only sucrose, glucose and fructose are present. During the cooking process, starch is hydrolysed into maltose by enzymes (a-amylase and b-amylase) and there are significant differences between varieties for the level of starch conversion into maltose (Walter et al 1975;Picha 1985). Some varieties which are not sweet when raw do not stay non-sweet after cooking due to maltose.…”
Section: Introductionmentioning
confidence: 99%
“…High Performance Liquid Chromatography (HPLC) is the most commonly used technique to quantitate maltose, sucrose, glucose and fructose in cooked sweet potatoes (Waramboi et al 2011). Unfortunately, HPLC is fairly time consuming as samples have to be injected one after the other through the column and the elution time is at least 10 min per sample (Picha 1985). Gas chromatography (GC) has also been used to analyse sugars in cooked samples (Horvat et al 1991;Kays et al 2005) with similar technical constraints.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation